Conversion of Biomass-Derived 2-Hexanol to Liquid Transportation Fuels: Study of the Reaction Mechanism on Cu–Mg–Al Mixed Oxides - Luggren, Pablo Jorge (2015)
The reaction mechanism of 2-hexanol conversion to high molecular weight compounds to be used as liquid transportation fuels was studied on MgO, Cu/SiO2 and a bifunctional Cu-Mg-Al mixed oxide with 8 wt. % Cu (catalyst 8.0CuMgAl). Catalysts were characterized by several physical and spectroscopic techniques. The evolution of 2-hexanol conversion and yields in inert (N2) and reducing (H2) reaction atmospheres at different contact times (W/F0) was investigated, which allowed distinguishing between primary and secondary products. In H2, at W/F0 = 500 g h/mol, the bifunctional 8.0CuMgAl catalyst yielded more than 90 % of branched C9-C24 oxygenates and hydrocarbons that were obtained via sequential steps comprising dehydrogenation, C-C coupling, dehydration and hydrogenation reactions. The metal-base bifunctional nature of this reaction network on 8.0CuMgAl was elucidated: nano-sized Cu0 particles promote dehydrogenation and hydrogenation steps whereas Mg-O pairs participate mainly in C-C coupling reactions. The product distribution depended on the reaction atmosphere. In H2, the reaction pathways leading to formation of even carbon atom number products (C12, C18 and C24) were favored and hydrocarbons were the main products at high conversion levels. In N2, significant amounts of odd carbon atom number products (C9, C15 and C21) were formed with a higher contribution of oxygenates to the product pool.